Limits of legality the ethics of lawless judging - Brand-Ballard, Jeffrey (New York ; Oxford : Oxford University Press, 2010)
Combining ethical theory with discussions of caselaw, Jeffrey Brand-Ballard challenges arguments for the traditional view including arguments from the fact that judges swear oaths to uphold the law, and arguments from our duty to obey the law among others.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Judicial ethics -- United States; Judicial corruption -- United States; Rule of law -- United States